1994
DOI: 10.1139/x94-123
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of subalpine fir (Abieslasiocarpa) following fire: effects of climate and other factors

Abstract: Subalpine fir (Abieslasiocarpa (Hook.) Nutt.) regeneration following fire was studied at two locations that burned in 1902 northeast of Mount Rainier, Washington. Tree establishment dates were compared with local climatic records using multiple and logistic regression to identify potential relationships between seasonal climate and annual tree establishment. The influence of microsite features on forest regeneration was also explored. Little regeneration occurred in the first 30 years after the fires, and most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 0 publications
3
70
1
Order By: Relevance
“…These sites are usually steep, south-facing slopes, and colonization lags substantially (30 to 50 years), with most regeneration occurring during wetter than normal summers. Little (1992) found that, on burned sites, extended growing seasons created by early snowmelt in spring and wetterthan-normal summers is associated with tree establishment. In the east Cascades, both of these patterns may exist, and they may be accompanied by yet a third pattern.…”
Section: Grasslands Shrublands and Woodland Ecosystems-the Perenniamentioning
confidence: 96%
“…These sites are usually steep, south-facing slopes, and colonization lags substantially (30 to 50 years), with most regeneration occurring during wetter than normal summers. Little (1992) found that, on burned sites, extended growing seasons created by early snowmelt in spring and wetterthan-normal summers is associated with tree establishment. In the east Cascades, both of these patterns may exist, and they may be accompanied by yet a third pattern.…”
Section: Grasslands Shrublands and Woodland Ecosystems-the Perenniamentioning
confidence: 96%
“…However, other studies show that a northern aspect favors fir regeneration [22,26]. Moisture stress can be a critical factor limiting conifer regeneration in dry coniferous forests and is usually higher in sites of high solar radiation [14,17,21,25). Our observations can be partially explained due to the fact that Greek fir is considered one of the best drought-adapted European firs [27].…”
Section: Discussionmentioning
confidence: 62%
“…Highly stress-tolerant conifers in subalpine and alpine meadows can facilitate establishment by less tolerant (but potentially more competitive) tree species by ameliorating stress from deep snowpack, cold temperatures, or high light levels, or by reducing competition from herbaceous vegetation (Bansal et al 2011, Little et al 1994, Stueve et al 2009, Zald et al 2012. For example, subalpine fi r trees are often able to establish under the canopies of large subalpine larch or whitebark pine trees and, being more shade tolerant, may later be able to grow up through the canopy and overtop the pioneer tree Habeck 1972, Tomback et al 2001).…”
Section: Biotic Interactionsmentioning
confidence: 99%
“…Wildfi res are infrequent in subalpine forests, as deep snowpacks produce a very short fi re season, fuels are often wet, and spatial discontinuities can inhibit fi re spread (Agee 1993). However, forest vegetation can be dramatically altered by rare wildfi re events, as recovery from stand-replacing wildfi res can be very slow (Little et al 1994). In fact, it can take decades to centuries for tree reestablishment in burned subalpine forests that do not include lodgepole pine (Agee and Smith 1984, Little et al 1994.…”
Section: Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation